PENGARUHPUPUK KANDANG AYAM TERHADAP SERAPAN FOSFORDAN HASIL TANAMANKUBIS BUNGA (Brassica oleraceavar. botrytis L.) PADA OXICDYSTRUDEPTS LEMBANTONGOA - R Pali, Imam Wahyudi, Ulfiyah A Rajamuddin, Fadlia (AGROTEKBIS, 2015)
This research aimed to identify the effect of different rates of chicken manure on phosphorous uptake (P) and cauliflower yield in Oxic dystrudepts of Lemban Tongoa. This research was aranged a Randomized Block Design (RBD) with the chicken manure  rates as the treatments i.e. control or with no chicken manure added, 10 t ha-1, 15 t ha-1, 20 t ha-1, 25 t ha-1, 30 t ha-1, and 35 t ha-1. Each treatment was replicated three times, there were 21 experimental units. The result of research showed that adding chicken manure can increase plant uptake of P, this is in line with the significantly increasing plant dried weight and phosphor concentration in the plant tissue. The addition of chicken manure can increase pH (H2O), C-organic content, P-total and P-available but decrease Al-exchangeable.